A step forward in solvent knitting strategies: ruthenium and gold phosphine complex polymerization results in effective heterogenized catalysts. Issue 17 (25th July 2019) - Valverde-González, Antonio; Marchal, Gwendoline; Maya, Eva M.; Iglesias, Marta
Abstract : A knitting strategy has been applied to obtain metal–phosphine porous organic polymers (Kphos(M)), resulting in effective heterogenized catalysts for different reactions. Abstract : Porous polymers based on ruthenium and gold triphenylphosphine complexes (KPhos(Ru), KPhos(Ru)Bi, KPhos(AuCl) and KPhos(AuNTf2 )) were prepared via a cost-effective solvent knitting method with [RuHClCO(PPh3 )3 ] or AuXPPh3 (X = Cl, NTf2 ) as single monomers or combined with biphenyl, which represents a further approach to obtain heterogenized catalysts. The resulting materials mainly preserve the metal coordination environment of their parent complexes, are stable up to 350 °C and have reasonable surface areas (250–300 m 2 g −1 for KPhos(Ru)-polymers). KPhos(Ru)s selectively catalyze the imination of alcohols in the presence of base and the results for KPhos(Au)s show they are effective for the intermolecular hydration and hydroamination of alkynes. These materials can be reused several times without significant loss of activity. This novel and simple method affords heterogenized catalysts that combine the reactivity and selectivity of their homogeneous counterparts with the stability and reusability of a heterogeneous framework.